Workshop Ketukangan Material Bambu Untuk Inovasi Bangunan Modern Berbasis Kepariwisataan di Dataran Tinggi Gayo, Aceh - Wulandari, Elysa; Widyojatmoko, Andry; Permana, Asep Yudi; Sari, Laina Hilma; Agustina, Sylvia; Djamaludin, Masdar; Sabila, Farisa; Arafat, Pratitou; Mardhatillah, Rizqi; Aditya, Atika (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
Bamboo is very abundant in the Gayo Highlands, but locals mostly use it for simple things like temporary shelters in rice fields and fences around houses. In the past, before modern materials became widely available, bamboo played a significant role in traditional Gayo buildings, both structurally and culturally. A three-day bamboo workshop was held to revive bamboo as a versatile, sustainable building material for modern architecture, while preserving its cultural significance. The workshop had two main goals: teaching how bamboo can work with modern materials like steel and cement, and showing new designs for tourism buildings using bamboo. Participants learned how to process bamboo, connect pieces, and preserve it. They also created new building ideas combining bamboo with other materials. The workshop helped the community understand bamboos environmental, cultural, and economic importance, supporting sustainable tourism and contributing to global goals for sustainable cities and responsible use of resources.